PERAN KINERJA ENVIRONMENTAL, SOCIAL AND GOVERNANCE (ESG) DAN KEPEMILIKAN INSTITUSIONAL DALAM MENINGKATKAN NILAI PERUSAHAAN - Angelina Verity Iskandar; Mitha Dwi Restuti (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2026)
Sustainability has emerged as a central consideration for investors, stakeholders and society, driving firms to balance financial performance with long-term responsibility. The growing integration of the Sustainable Development Goals (SDGs) into investment decision making further amplifies the strategic importance of Environmental, Social, and Governance (ESG) practices. This study examines the effect of ESG performance and institutional ownership on firm value among firms listed on the Indonesia Stock Exchange (IDX). Using a sample of 446 firm-year observations from 2014 to 2022, with ESG score obtained from Refinitiv Eikon, the analysis is conducted using Generalized Least Squares (GLS) method. The findings reveal that ESG performance positively influences firm value, suggesting that firms with stronger ESG practices are better positioned to achieve sustainable growth and mitigate long-term risks. In addition, institutional ownership is found to enhance firm value, highlighting the effective monitoring role of institutional investors in improving corporate performance. These results underscore the strategic importance of ESG integration and ownership structure in driving firm value, particularly in emerging markets.